Experimental Study of a Ground Vortex - Barata, Jorge M M (2009)
Laser-Doppler measurements of the mean and turbulent components of the velocity flowfield resulting from the frontal collision of a wall jet with a boundary layer are presented and discussed, together with the visualization of the flow with direct photography and digital film imaging. The experiments were carried out for boundary-layer-to-wall- jet velocity ratios of 0.5 and 0.58. The results revealed the existence of a small counter-rotating recirculating zone located upstream (in the sense of the wall-jet flow) of the separation point, not reported before for this type of flow. This secondary vortex has an oscillating behavior observed in other ground-vortex flows, similar to that which can be observed, namely, through the bimodal histogram of the horizontal velocity (parallel to the wall) measurements, although the power spectra measurements do not exhibit any particular peaks.